Advances in motivation in sport and exercise - Roberts, Glyn C.; Treasure, Darren C. 1965- (Champaign, IL Human Kinetics, 2012)
Advances in Motivation in Sport and Exercise, Third Edition, presents the most current information in sport and exercise motivation, including discussion of new research surrounding self-determination theory and goal achievement theory, traditional topics of goal setting and self-efficacy, and newer areas of attention such as passion and perfectionism. Readers not only will gain knowledge in one of the leading areas of sport psychology research but also learn how the research can inform their current practice. In this third edition, editors Glyn Roberts and Darren Treasure, along with a highly respected team of contributors, offer sport and exercise psychology researchers and students the most up-to-date review of the state of research in motivation. As in previous editions, the text chronicles the growth of motivation research and its role in physical activity, exercise, and sport. The star team of contributors offers thoughtful discussion of key issues and findings for readers to consider and insight into both the conceptual understanding of motivation and its application. Advances in Motivation in Sport and Exercise, Third Edition, begins by introducing readers to new trends and interpretations in motivational theory. Each chapter of the text discusses a unique motivational theory and its contemporary contribution to the field of knowledge. Whether research or practically inclined, readers will be enlightened through the use of these features: Presentation of differing perspectives and approaches that make up the current state of research in the most vibrant of topics in sport and exercise psychology; Future Directions for Research and Practical Applications sections at the end of each chapter that help demonstrate how the chapters' content is applied to real-world practice; An extensive reference list that serves as a tool for finding further resources and continuing study of motivation. The third edition of Advances in Motivation in Sport and Exercise helps readers learn how the theories of motivation can be applied in exercise, sport, and physical activity contexts. Thoughtfully compiled by a respected editor and contributor team, this comprehensive text serves as a review of current research and a resource for further study and applications for researchers, students, and practitioners
Part I: Contemporary Theories of Motivation : New Directions and Interpretations -- Chapter 1. Motivation in Sport and Exercise From an Achievement Goal Theory Perspective : After 30 Years, Where Are We? / Glyn C. Roberts -- Motivation and Achievement Behavior -- Motivational Implications of Task or Ego Involvement -- Evidence Summary -- Counterarguments -- Counterpoints to the Counterarguments -- Parsimony, Elegance, and Conceptual Coherence in Sport Psychology -- And the Point Is? -- Practical Applications -- Directions for Future Research -- Summary -- Chapter 2. The Place of Achievement Goals in the Social Context of Sport : A Comparison of Nicholls' and Elliot's Models / Athanasios G. Papaioannou, Nikos Zourbanos, Haralampos Krommidas, and George Ampatzoglou -- Review on Trichotomous and Two-by-Two Findings in Sport -- A Comparison Between Elliot's and Nicholls' Models -- Interpretation of Findings Based on the Trichotomous and Two-by-Two Models -- Practical Applications -- Directions for Future Research -- Summary -- Chapter 3. A Self-Determination Theory Perspective on Motivation in Sport and Physical Education : Current Trends and Possible Future Research Directions / Nikos Ntoumanis -- Sociocontextual Environment -- Satisfaction and Thwarting of Psychological Needs -- Practical Applications -- Directions for Future Research -- Summary -- Chapter 4. Perfectionism: A Foundation for Sporting Excellence or an Uneasy Pathway Toward Purgatory? / Howard K. Hall, Andrew P. Hill, and Paul R. Appleton -- Perfectionism in Elite Sport Performers -- Definition -- Empirical Evidence of Perfectionism in Sport -- Practical Applications -- Directions for Future Research -- Summary -- Chapter 5. The Dualistic Model of Passion in Sport and Exercise / Robert J. Vallerand -- Psychology of Passion -- Initial Research on the Concept of Passion -- Development of Passion -- Passion and Intrapersonal Outcomes -- Passion and Interpersonal and Intergroup Outcomes -- Passionate Functioning Under Various Situations -- Practical Applications -- Directions for Future Research -- Summary -- Chapter 6. Goal Setting to Enhance Motivation in Sport / Glyn C. Roberts and Elsa Kristiansen -- Goal Setting -- A Search for Theory -- Achievement Goal Theory -- Goal Involvement -- Achievement Goal Orientations -- Motivational Climate -- Achievement Goal Theory and Goal Setting -- Why Goal Setting Works -- Managing the Motivation of Others -- Goal Setting as a Motivational Strategy for Injuries and Rehabilitation -- Managing Individual Motivation -- Practical Applications -- Directions for Future Research -- Summary -- Part II: Understanding the Psychological Determinants and Mediators of Physical Activity Behavior -- Chapter 7. Self-Determination Theory and Exercise Motivation: Facilitating Self-Regulatory Processes to Support and Maintain Health and Well-Being / Martyn Standage and Richard M. Ryan -- Basic Components of SDT and Mapping of Minitheories -- Self-Determination Theory in Exercise Science Research -- Practical Applications -- Directions for Future Research -- Summary -- Chapter 8. Self-efficacy and Motivation in Physical Activity and Sport: Mediating Processes and Outcomes / Todd A. Gilson and Deborah L. Feltz -- Theoretical Overview of Self-Efficacy -- Individual-Level Self-Efficacy Research -- Collective Efficacy Research -- Coaching Efficacy Research -- Practical Applications -- Directions for Future Research -- Summary -- Chapter 9. Social Cognitive Approaches to Understanding Exercise Motivation and Behavior in Cancer Survivors / Jeff K. Vallance and Kerry S. Courneya -- Cancer Treatments -- Exercise and Cancer Survivorship -- Physical Activity Prevalence in Cancer Survivors -- Exercise Motivation in Cancer Survivors -- Exercise Behavior in Cancer Survivors -- Theory of Planned Behavior -- Social-Cognitive Theory -- Self-Determination Theory -- Exercise Beliefs Among Cancer Survivors -- Practical Applications -- Directions for Future Research -- Summary -- Chapter 10. Understanding Exercise Behavior : A Self-Presentational Perspective / Kathleen A. Martin Ginis and Diane Mack -- Background -- Evidence -- Theoretical Perspectives on Self-Presentation and Exercise Motivation -- Role of Self-Presentation in Exercise Motivation -- Practical Applications -- Directions for Future Research -- Summary -- Chapter 11. Interventions for Physical Activity and Sedentary Behavior / Stuart J.H. Biddle, Nanette Mutrie, Trish Gorely, and Avril Blamey -- Role of Motivation: Understanding the Ecological and Behavioral Epidemiology Frameworks -- Theories Typically Used in Physical Activity Interventions -- Types and Settings for Interventions -- Behavior Change: Issues of Theory and Interventions -- A Framework for Evaluating Interventions -- Intervention Planning and Evaluation -- Examples of Physical Activity Behavior Change -- Sedentary Behavior Change -- Practical Applications -- Directions for Future Research -- Summary
Includes bibliographical references
Keywords: Social perception; Exercise -- Psychological aspects; Sports -- Psychological aspects